2011
DOI: 10.1371/journal.pone.0022451
|View full text |Cite
|
Sign up to set email alerts
|

Dogs Leaving the ICU Carry a Very Large Multi-Drug Resistant Enterococcal Population with Capacity for Biofilm Formation and Horizontal Gene Transfer

Abstract: The enterococcal community from feces of seven dogs treated with antibiotics for 2–9 days in the veterinary intensive care unit (ICU) was characterized. Both, culture-based approach and culture-independent 16S rDNA amplicon 454 pyrosequencing, revealed an abnormally large enterococcal community: 1.4±0.8×108 CFU gram−1 of feces and 48.9±11.5% of the total 16,228 sequences, respectively. The diversity of the overall microbial community was very low which likely reflects a high selective antibiotic pressure. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 91 publications
6
51
4
Order By: Relevance
“…AMR frequencies found in the present survey were overall higher when compared with the above studies, with the exception for Ghosh and others 2011, probably because intensive care unit animals under AM treatment were sampled in that study. Jackson and others (2009) have included nasal, belly, teeth and hindquarters sites for sampling in their study.…”
Section: Discussioncontrasting
confidence: 65%
“…AMR frequencies found in the present survey were overall higher when compared with the above studies, with the exception for Ghosh and others 2011, probably because intensive care unit animals under AM treatment were sampled in that study. Jackson and others (2009) have included nasal, belly, teeth and hindquarters sites for sampling in their study.…”
Section: Discussioncontrasting
confidence: 65%
“…This is also why it was decided to fully characterized these dog strains and compare them with human strains from Canada. In canines, reports have indicated that ARE most frequently were of ST266 origin but that a variety of STs associated with human clinical infections could also be found (Damborg et al, 2008, 2009; Ghosh et al, 2011; De Regt et al, 2012). These findings, along with the current study, present evidence of some genotypic concordance, based on MLST, between hospital clones of human origin and community ARE from clinical cases of dogs, indicating that these isolates are likely evolutionarily linked.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies around the world (Damborg et al, 2008, 2009; De Regt et al, 2008, 2012; Ossiprandi et al, 2008; Jackson et al, 2009; Kwon et al, 2012) have revealed that healthy dogs are known community reservoirs where some of these typical hospital clones seem to reside. Furthermore, HA ARE have been recovered from clinical cases of urinary tract infections in canines from the U.S. (Simjee et al, 2002), Korea (Kwon et al, 2012) and Denmark (Damborg et al, 2008) and from feces of canines leaving the intensive care unit of an American veterinary medicine teaching hospital (Ghosh et al, 2011). In general, only limited data is available on lineages and genotypic content of HA ARE from canine clinical isolates.…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1980's the emergence of Hospital associated Ampicillin resistant Enterococci (ARE) in USA preceded rise of vancomycin resistance in enterococci, which happend in the 1990s, is the reason why virtually all VRE of nosocomial infections in humans are also ampicillin resistant (Grayson et al, 1991) but ARE associated with human infections remain vancomycin susceptible (Tremblay et al, 2013). The hospital associated ARE have been recovered from dogs suffering from urinary tract infections in US (Simjee et al, 2002), Denmark (Damborg et al, 2009), Korea (Kwon et al, 2012) and also from the faeces of dogs departing the intensive care unit of an American veterinary medicine teaching hospital (Ghosh et al, 2011). In a study conducted in veterinary teaching hospital of Canada with the objective of characterizing the ARE strains of dogs and human revealed the cross-transmission between humans and dogs and further supports the significance of antibiotic stewardship to avoid zoonotic spread of canine ARE (Tremblay et al, 2013).…”
Section: Multidrug-resistant Enterococcimentioning
confidence: 99%